Panorama Economico in the context of the international visibility of scientific journals (2015)
Assessment of scientific journals in the National Bibliographic Index Publindex represented a continuous improvement in terms of quality of national academic journals. Nevertheless, this process came along inconsistencies between national standards and international requirements.